Study of endometrial Status of Patients with Abnormal Uterine Bleeding in Patan Hospital - Shrestha, Sabina; Sigdel, B (Journal of College of Medical Sciences-Nepal, 2014)
Background: Abnormal uterine bleeding may be defined as changes in frequency of menstruation, duration of flow or amount of blood loss. Early accurate diagnosis and proper treatment is essential to prevent progress to endometrial cancer. Objective: This study was done to evaluate the histopathology of endometrium for identifying the endometrial causes of abnormal uterine bleeding. Method: This was a retrospective study done in department of pathology, Patan Hospital from 1 August 2011- to 31 July 2012; total 413 cases were included in this study. Results: The age of the patients ranged from 19 to 70 years. The most common clinical presentation was menorrhagia (47.46%), followed by continuous bleeding (14.04%) and metrorrhagia (13%). The commonest histopathological diagnosis was secretory endometrium 128 cases (30.99%), followed by proliferative endometrium 91 cases (22.03 %). Secretory endometrium was most commonly (52 cases) observed in 41-50 years age group followed by 43 cases in 30-40 years age group. Similarly proliferative endometrium was also most commonly seen in 41-50 age group (44 cases) followed by 31-40 years of age group (32cases). Malignant disease was most commonly seen in 51-60 years age group. Conclusions: Abnormal uterine bleeding is most common in 21-30 years age group.The most common clinical presentation is menorrhagia followed by continuous bleeding. Secretory endometrium is the most common histopathological findings. Malignancy is more common in postmenopausal group. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 20-24 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9683